RESULTS OF ECOPRINT MOTIFS BASED ON DIFFERENCES IN TYPES OF FABRIC, LENGTH OF TIME, TYPES OF MORDANTS, AND TYPES OF NATURAL DYES - Nida, Safwatun; Rosa Fadilla, Silvya; Pranata, Ivandra Bagus; Sari, Shinta Permata; Nugraheni, Dian (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2024)
Biodiversity of flora in Indonesia greatly supports the development of textile products, ecoprint is one of the textile products that involves the utilization of this diversity. Various types of plants found in the surrounding environment can be used as dyes for making ecoprints. Ecoprint is a color transfer technique on fabric which in the manufacturing process requires a mordant to bind plant colors to the fabric. This study aims to determine the effect of variations in fabric type, length of time, type of mordant, and type of natural dye on ecoprint color expression. This experiment used the steaming technique in ecoprint to transfer motifs and colors to fabric. In this study, three types of fabric were used, namely: toyobo cotton, mori, and blanco. Variants of steaming time were tested at intervals of 60 minutes, 90 minutes and 120 minutes. Variations in the types of mordant used are vinegar and alum. Meanwhile, the types of natural dyes used are jolawe, soga, and secang. The results of the research show that there are differences in color expression produced by vinegar and alum mordant substances. Alum mordant produces intense color expression and clear form. Leaf motifs can be printed well on toyobo cotton fabric. Variations in steaming time in this study did not produce significant differences in color expression. Meanwhile, each natural dye produces a different color expression.